Participatory health research and promotion with migrant communities in Germany: a scoping review - Luetke Lanfer, Hanna; Landwehr, Janna; Reifegerste, Doreen (Frontiers in Public Health, 2025)
IntroductionParticipatory health research and promotion aims to foster inclusive knowledge production and address health inequities. Migrant communities, given their diverse backgrounds and health needs, are regularly engaged in PHR/P. However, the extent and ways of their participation across research phases and the integration of critical reflections in published studies from Germany remain underexplored.MethodsThis scoping review followed Arksey and O’Malley’s framework and adhered to PRISMA guidelines. Four databases were systematically searched for eligible studies. A total of 17 publications representing 13 projects were included and analysed using a structured codebook.ResultsMigrants’ participation was described unevenly across different phases of the research process, with more frequent engagement in operational aspects such as data collection than in research design, analysis, or dissemination. Reflexivity was inconsistently reported. While some studies provided theoretical reflections on participation, explicit links to how these reflections shaped to research practices were often missing. Reflections also focused more on methodological and external challenges than on power dynamics, ethics, or researcher positionality.DiscussionSince our analysis is based on published accounts, the extent to which participation and reflexivity were practiced beyond what was documented remains unclear. More systematic documentation of participatory processes and reflexivity would enhance transparency, reflect the complexities of PHR/P with migrants more deeply, and inform future practice.